Biodegradation of High Density Polyethylene and Poly (l) Lactic Acid Blends - Khare, Onam (My University, 2013)
The blends of HDPE-PLLA in different ratios were tested for the degree of biodegradation as per ASTM D 5338 (2003) standard, which is the “Standard Test Method for Determining Aerobic Biodegradation of Plastic Materials under Controlled Composting Conditions”. The samples (along with their composition and tensile strength) were provided by the Department of Chemical Engineering. A total of six bioreactors (containing one ‘blank’ and five film samples of blends of HDPE/PLLA in ratios 100/0, 95/5, 90/10, 80/20 and 75/25 respectively) were used. The CO2 free air was supplied to the bioreactors (under pressure) through six rotameters, one for each of the bioreactors. The temperature of the bioreactors was maintained at 37°C by placing them in an air circulated incubator. The carbon of the polymer samples got converted into CO2 by its aerobic degradation with the help of microorganisms present in the composted municipal solid wastes (ued as inoculums). The amount of CO2 evolved was calculated at the time intervals of 12 hr, 24 hr, 48 hr, and 96 hrs by using phenophthelein indicator and titration against HCl solution. The blend PB5 (HDPE/PLLA = 75/25) showed the maximum biodegradation, which may be due to the reason that it contained the highest amount of the biodegradable polymer PLLA. The sample PB1 (HDPE/PLLA = 100/0) showed the minimum biodegradation.
M.Tech (EST) Dissertation
Keywords: HDPE; PLLA; CO2; Degradation